2019
DOI: 10.14569/ijacsa.2019.0100503
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Associated with Voucher Program for Speech Language Therapy for the Preschoolers of Parents with Communication Disorder using Weighted Random Forests

Abstract: It is necessary to identify the demand level of consumers and recognize the support target priority based on it in order to provide efficient services with a limited budget. This study provided baseline data for spreading the use of consumeroriented voucher service by exploring factors associated with the demand of the Voucher Program for Speech Language Therapy for preschool children. This study were analyzed 212 guardians living with children (≤5 years old) who resided in Seoul from Aug 11 to Oct 9, 2015. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This method is motivated by the potential instability of averaging predictions of trees. Byeon et al [15] used Out-of-Bag (OOB) samples for deriving Akaike weights while averaging the tree results. Based on the proposed algorithm they analyzed in-depth the consumers' demand level in order to operate "the Voucher Program for Speech Language Therapy" efficiently and for suggesting different ways to improve the special education service support.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is motivated by the potential instability of averaging predictions of trees. Byeon et al [15] used Out-of-Bag (OOB) samples for deriving Akaike weights while averaging the tree results. Based on the proposed algorithm they analyzed in-depth the consumers' demand level in order to operate "the Voucher Program for Speech Language Therapy" efficiently and for suggesting different ways to improve the special education service support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pruning of individual trees in the forest [12,13]; • Weighing individual trees [11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Pham and Olafsson [ 44 ] weighted each tree by replacing the regular average with a Cesaro average. Weighting based on the variable performance and importance was developed by Byeon et al [ 45 ] and Booth et al [ 46 ]. Finally, Utki et al [ 47 ] created a weighted random survival forest by assigning weights to survival decision trees or to their subsets.…”
Section: Preliminariesmentioning
confidence: 99%
“…Previous studies [1,10,11,12,13] that evaluated the factors related to geriatric depression in South Korea local communities reported that health, socioeconomic status, education level, age, spouse, and social activities affected geriatric depression. Since regression analysis was mainly used as a modeling method to predict depression, they were efficient in identifying individual risk factors [14,15]. However, they were limited in identifying compound-risk factors (multivariate) such as sociodemographic variables and living habits [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since regression analysis was mainly used as a modeling method to predict depression, they were efficient in identifying individual risk factors [14,15]. However, they were limited in identifying compound-risk factors (multivariate) such as sociodemographic variables and living habits [14,15]. Moreover, since regression analysis assumes independence, normality, and homoscedasticity, there is a possibility of producing biased results when the model is developed using data in violation of normality [16].…”
Section: Introductionmentioning
confidence: 99%